Developing Thai Students' English Speaking Skills and Self-Confidence Through the English Competition Program - Belly Ubaidila; Tarisa Amalia Dwi Arisanti; Dwi Mutiara Jelita; Karin Wahyu Cahyaningrum; Nabiela Naily; Aris Fanani (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2025)
Enhancing English speaking skills is crucial for global communication, particularly at Santi Witya Serong School in Thailand. This study implements the English Competition Program as an innovative strategy distinct from conventional learning by incorporating competition-based and interactive activities. The research examines its effectiveness in improving students’ speaking skills and confidence. Applying Asset-Based Community Development (ABCD) theory, the program utilizes school resources—teachers, students, and learning culture—as key assets for language development. Using a qualitative approach, data were collected through observations, interviews with teachers, and document analysis of competition results. The program includes three competitions: spelling bee for grades 1–2, guessing vocabulary for grades 3–4, and introduction speaking for grades 5–6. The findings indicate that competition-based learning significantly improves English proficiency in the form of speaking and confidence. The study recommends continuous implementation and evaluation to optimize the program. This study presents a novel approach, demonstrating that competition-driven methods can effectively enhance students’ communication skills.